THE AIR QUALITY AND NOISE STUDY IN SETTLEMENTS AND METAL SCRAP MELTING FACTORY - Wahid Giantara; Tugiyono Tugiyono; Agus Setiawan; Gregorius Nugroho Susanto (Department of Biology Faculty of Mathematics and Natural Sciences Universitas Lampung in collaboration with The Indonesian Association of Biology (PBI) Lampung Branch., 2021)
Air is an important component for the survival of living things, especially humans. However, air quality has decreased due to pollution. The harmful elements that enter the atmosphere are Carbon Monoxide (CO), Nitrogen Dioxide (NO2), Sulfur Dioxide (SO2), Particulates (PM10), and Ozone (O3). Noise is defined as unwanted sound or sound so that it disturbs and endangers health. Sources of noise are divided into moving and stationary noise sources. The method used in this research is grab sampling by installing an air sampler impinger to capture particles or pollutants as well as taking noise data using a simple method with a Sound Level Meter with a reading every 5 seconds within 10 minutes for one measurement. The results showed that the air quality in residential and workspace areas was still within quality standards. The noise level in residential areas is still acceptable, but the noise level in the production room surpasses the acceptable limit.